2016
DOI: 10.1007/s10886-016-0775-y
|View full text |Cite
|
Sign up to set email alerts
|

d-Pinitol in Fabaceae: an Oviposition Stimulant for the Common Grass Yellow Butterfly, Eurema mandarina

Abstract: The common grass yellow butterfly, Eurema mandarina (formerly Eurema hecabe mandarina) (Lepidoptera, Pieridae), recently has been separated taxonomically from a subtropical population of Eurema hecabe in Japan. This species is widely distributed in the temperate region of Japan, and feeds mainly on various ligneous plants within the Fabaceae. We attempted to identify an oviposition stimulant for E. mandarina from its primary hosts, Albizia julibrissin and Lespedeza cuneata. In both hosts, crude extract and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Under the same conditions of reversed‐phase flash column chromatography, this cyclitol is demonstrated to elute in the aqueous subfraction Tr‐3‐1, and its estimated concentration is 0.54% of fresh leaf weight (Honda et al ., ). We have previously reported that 0.5% (w/v) d ‐pinitol elicits 60% oviposition responses from E. mandarina females (Mukae et al ., ). Consequently, it is reasonable to conclude that the high oviposition responsiveness of E. mandarina to Tr‐3‐1 is attributed to d ‐pinitol.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Under the same conditions of reversed‐phase flash column chromatography, this cyclitol is demonstrated to elute in the aqueous subfraction Tr‐3‐1, and its estimated concentration is 0.54% of fresh leaf weight (Honda et al ., ). We have previously reported that 0.5% (w/v) d ‐pinitol elicits 60% oviposition responses from E. mandarina females (Mukae et al ., ). Consequently, it is reasonable to conclude that the high oviposition responsiveness of E. mandarina to Tr‐3‐1 is attributed to d ‐pinitol.…”
Section: Discussionmentioning
confidence: 97%
“…Oviposition responses of females to the extract of T. repens leaves, its fractions and authentic samples were examined by the same method reported previously (Mukae et al ., ). An artificial plant model (height 8 cm) with 12 round‐shaped leaves (40–135 mm 2 ) was used as a surrogate for sample deposition.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is found in conifers, legumes (Fabaceae) and Caryophyllales such as Simmondsia chinensis ( Angyal and Macdonald, 1952 ; Dittrich and Korak, 1984 ; Guo and Oosterhuis, 1995 ; Chiera et al, 2006 ). D-pinitol induces oviposition of the Grass Yellow Butterfly Eurema mandarina ( Mukae et al, 2016 ). However, an influence of pinitol from the phloem of alfalfa on phloem-feeding pea aphid could not be found ( Campbell and Binder, 1984 ).…”
Section: Discussionmentioning
confidence: 99%
“…Possible proximate cues for T. yuccasella to reject distal flowers with basal fruits as oviposition sites include tactile and/or chemical cues from fruits and/or flowers. There is overwhelming empirical evidence to show that many lepidopterans use multiple plant‐based cues to identify suitable oviposition sites and reject unsuitable ones, both within and between host plant species (reviewed in Renwick & Chew, ; Wennström et al., ; Ryuda et al., ; Mukae et al., ). Identifying specific cues that females use to respond to the presence of basal fruits is an avenue for further research.…”
Section: Discussionmentioning
confidence: 99%